The The factors related to drop out events pulmonary tuberculosis treatment in Nabire district Papua province - Sukatemin; ester; Abraham Marai (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2022)
Background: Tuberculosis (TB) is still the biggest threat to health in the world, in addition to the increasing number of cases, the incidence of death due to tuberculosis also continues to increase, recorded in 2012 there were 8.7 million cases with a death rate of 4.1 million people. The national program for tuberculosis control continues to be promoted with the discovery of new cases in Papua province in 2017 amounting to 85% of the national target, case findings are not comparable to treatment success, where patients who are successful in treatment are only 60%, the rest are declared failed in treatment.Research purposes: This study aims to determine the factors associated with the incidence of drop out of pulmonary tuberculosis treatment, including family support, support from health workers, difficulty in accessing health care facilities and factors of anti-tuberculosis drugs (OAT).Research methods: using a cross-sectional study with a case-control study approach, where the sample consisted of cases, namely patients who were declared to have failed to follow treatment, while controls were patients who had recovered from treatment. The number of each sample is 41 people so that n = 82 people. To find out the factors that cause drop out of treatment, statistical tests were carried out using the spearman's test, considering that the data presented were not normally distributed after going through the One-Sample-Kolmogorov-Smirnov-Test test.Result: based on the statistical test, the results of family support were 0.000, the support of health workers was 0.003, the difficulty of going to health facilities was 0.002 and the drug factor was 0.06, where P = <0.05.Conclusion: the Factors related to the incidence of tuberculosis treatment drop out in Nabire district are family support, difficulty in accessing health facilities while the drug factor is not the cause of the drop out of treatment, because there is no significant relationship between the drug factor and the incidence of drop out of tuberculosis treatment